Pre-service Elementary Teachers’ Attitudes towards Chemistry Course - Seçil Erökten (International Journal of Assessment Tools in Education)
The current research aims to investigate the attitudesof pre-service elementary teachers towards chemistry course according to theirgender and the type of high school that they graduated from. As a scanningmodel, the current study was conducted in spring semester of 2015-2016 academicyears with the students of Elementary Education Department at Faculty ofEducation in Pamukkale University. 99 students who were attending the chemistrycourse in their first year curriculum participated in the study. The datacollection tool was "Attitudes Towards Chemistry Course Scale" whichwas developed by Hançer, Uludağ and Yılmaz (2007). Whether the attitude scoresof participants changed according to gender and the high school that theygraduated from were tested with independent samples t-test and one-way ANOVA. Accordingto the analyses, the students were observed to have negative attitudes towardschemistry class and these negative attitudes did vary according to neithergender nor the high school that graduated from.